1992
DOI: 10.1177/014233129201400206
|View full text |Cite
|
Sign up to set email alerts
|

Experimental intercomparison of Coriolis mass flowmeters

Abstract: This paper presents the first results of a systematic experimental intercomparison of the metrological performances of seven Coriolis mass flowmeters that are commercially available in Italy. Each of them was mounted and tested with similar operating conditions in the IMGC primary flow calibration facilities, Which enabled the authors to vary some of the most significantly influential factors. The test fluid was water at room temperature, and the maximum flow rates were ranged between 2.8 and 4.5 kg/s, accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…(i) Pressure drops of the present generation of CMFs are still quite different from model to model, depending upon shape and size of the vibrating tubes (Cascetta et al, 1992), but now they appear to be more acceptable in most applications.…”
Section: Further Remarks and Conclusionmentioning
confidence: 96%
See 2 more Smart Citations
“…(i) Pressure drops of the present generation of CMFs are still quite different from model to model, depending upon shape and size of the vibrating tubes (Cascetta et al, 1992), but now they appear to be more acceptable in most applications.…”
Section: Further Remarks and Conclusionmentioning
confidence: 96%
“…resul-is 4.1 1 ~r~frad~.t~tc~r~ remarks All the flowmeters tested were identified by an alphabet letter, from 'A' to 'F'. The CMF named 'G' in Cascetta et al (1992) being now identified as 'F'.…”
Section: The Metrological Evaluation Programmementioning
confidence: 99%
See 1 more Smart Citation
“…However, this effect has been recognized by the industry and has been compensated for by using an internal temperature sensor and automatically adjusting the calibration for temperature. By the early 1990s, most of these types of flow meters on the market included temperature compensation (Cascetta et al, 1992).…”
Section: Coriolis Effect Flow Metermentioning
confidence: 99%
“…The Coriolis mass flowmeter (CMF) is a high-precision device utilized to measure the mass flow of fluid directly and has wide application in many industries, such as the petrochemical industry, food processing industry, etc. (Cascetta et al, 1992; Haneveld et al, 2010; Ma and Eidenschink, 2001; Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%